Primary ovarian leiomyoma in a patient with uterine leiomyoma - V. B. Tskhay; E. K. Grebennikova; I. S. Brekhova; N. M. Yametova; E. Sh. Dzhunagova (Медицинский вестник Юга России, 2024)
A small, unilateral tumor. Most ovarian leiomyomas (OLM) are benign, but can range from benign to borderline with malignant degeneration. In many patients, OLM are asymptomatic and are detected accidentally during surgery. In rare cases, OLM can be accompanied by severe symptoms as their size increases. This situation requires differentiation these formations from malignant ovarian tumors, which is more often observed during the perimenopausal and menopausal periods. Being discussed that the source of OLM is smooth muscle blood vessel cells, so more undiagnosed small asymptomatic OLMs can be expected. This article presents a clinical case of OLM in a 39-year-old woman operated for uterine myoma. In the case we presented the coexistence of uterine fibroids and ovarian leiomyoma, which subsequently received diagnostic confirmation.